Characterizing Ethical Decision-Making and Its Influences: Examining Higher Education Leaders in the United States - Shollenberger, Tara (ETHICS IN PROGRESS, 2015)
The ethical decision-making (EDM) process that leaders should follow to avoid scandals and unethical behavior is often overlooked. In addition, visit few studies have focused on EDM within higher education. Yet, educational leaders have an ethical responsibility due in part to increasingly diverse student populations enrolled that is having an impact on the growth of educational institutions. This exploratory study used the Delphi research technique to identify an EDM definition that leaders use to make ethical decisions and identify the environmental factors that influence their decisions as well as an EDM model within the U.S.